+0  
 
0
76
1
avatar

There are values A and B such that (Bx-11) / (x^2-7x+10) = A/(x-2) - 3/(x-5).

 

Find A+B

 Jun 1, 2021
 #1
avatar+121056 
+1

Note  that  ( x - 2) ( x - 5)  =  x^2 - 7x + 10

 

So....if we  multiply  both sides  both the  equation by the  polynomial we get  that

 

(B x  -  11)  =  A(x - 5)  - 3(x - 2)     simplify

 

Bx - 11  =  Ax  - 5A  - 3x  + 6

 

Bx  -11   =  (A - 3)x  + ( 6- 5A )

 

This implies  that

 

B   = A  - 3      ⇒   A   =  B + 3     (1)   

-11  = 6 - 5A      (2)

 

Sub (1)  into (2)

 

-11  = 6 -  5( B + 3)

-17  =  -5B - 15

-2  =  -5B

B  =  2/5

 

A = 2/5 + 3  =   17/5

 

A + B   =    17/5   +  2/5    =   19/5

 

 

cool cool cool

 Jun 1, 2021

31 Online Users

avatar
avatar